Predictors of Unsuccessful Crossing with the Novel Cutting Balloon in Calcified Lesions - Ishihara, Takayuki; Hata, Yosuke; Tsujimura, Takuya; Mano, Toshiaki; Toyoshima, Taku; Kurata, Naoya; Higashino, Naoko; Asai, Mitsutoshi; Iida, Osamu (Angioscopy, 2022)
Background: Cutting balloons are commonly used for the preparation of calcified lesions, but problems with crossability occasionally limit the use of these balloons. A novel cutting balloon was recently developed and reported to have improved crossability in clinical settings. However, the predictors of its unsuccessful crossing have been unclear. The aims of this study were to examine the delivery success rate and to identify the predictors of unsuccessful crossing with the novel cutting balloon.Methods and Results: We prospectively enrolled 502 calcified lesions treated with the novel Wolverine cutting balloon under the guidance of either intravascular ultrasound (IVUS) or optical coherence tomography (OCT). The primary study outcome was the balloon delivery success, which we defined as successful crossing to the target lesion immediately after the IVUS or OCT evaluation. A multivariate analysis evaluated the independent predictors for unsuccessful crossing. The balloon delivery success rate was 92.4%. The multivariate analysis showed that non-left anterior descending (non-LAD) lesions (odd ratio [OR] 2.27, 95% confidence interval [CI]: 1.09–4.71, p = 0.028) and previous history of percutaneous coronary intervention (PCI) (OR 2.46, 95% CI: 1.09–5.53, p = 0.029) were the independent predictors for unsuccessful crossing.Conclusion: The Wolverine cutting balloon demonstrated high crossability. However, we should device its usage for non-LAD lesions and patients with a previous history of PCI.